Frequency and impact of enteric hyperoxaluria in pediatric short bowel syndrome: a retrospective single centre study - Schaefer, Jan Thomas; Schulz-Heise, Susanne; Rueckel, Aline; Rauh, Manfred; Juengert, Joerg; Galiano, Matthias; Meier, Norbert; Woelfle, Joachim; Schiffer, Mario; Hoerning, André (Frontiers in Pediatrics, 2023)
Objectives The survival of pediatric patients with short bowel syndrome has improved in recent years. Enteric hyperoxaluria as a pathophysiological consequence has been hardly addressed so far. It can be associated with nephrolithiasis, nephrocalcinosis or even renal insufficiency. We assessed the prevalence of hyperoxaluria and its pathogenic consequences in a retrospective single centre study over the last 12 years. Methods We conducted an internal database search for all pediatric patients suffering from short bowel syndrome treated from 2010 to 2022 in the department of pediatric gastroenterology as well as the pediatric nephrology and dialysis unit. Out of 56 patients identified, 26 patients were analysed for etiology of short bowel syndrome, renal excretion of oxalate (24/26), remaining short bowel and large intestinal length as well as further clinical parameters such as eGFR, nephrocalcinosis/urinary stone formation or stool frequency. Results Hyperoxaluria was detected in 14/26 patients (54%). Nephrocalcinosis was present in four patients. Out of these four patients, hyperoxaluria could be proven (21% of all hyperoxaluric patients) in three cases, one hyperoxaluric patient had nephrolithiasis (7%). In one patient hyperoxaluria lead to end stage renal disease. We found that 80% of patients with volvulus developed enteric hyperoxaluria. None of the investigated factors had an effect on oxalate excretion. Conclusion Enteric hyperoxaluria is a relevant pathophysiological finding in patients with short bowel syndrome occurring in about 50% of our cohort with multiple pathogenic complications. Regular screening for hyperoxaluria may be implemented in medical care for patients with short bowel syndrome. If necessary, prophylaxis, e.g., dietary advice or metaphylaxis should be initiated.